2005
DOI: 10.1089/dis.2005.8.35
|View full text |Cite
|
Sign up to set email alerts
|

A Matched-Cohort Study of Health Services Utilization Outcomes for a Heart Failure Disease Management Program

Abstract: Chronic disease is the leading cause of illness, disability, and death in the United States, affecting nearly 100 million Americans. Heart failure alone affects nearly 4.9 million Americans, with another 550,000 newly diagnosed cases each year. The aim of this study was to investigate the program effects of a heart failure care support program. A two-group cohort study matching on propensity scores was used to investigate 277 heart failure care support program participants and corresponding matched non-partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies have shown that DM programs reduce hospital admissions, 3,[5][6][7][8] length of stay, [5][6][7] emergency room visits, 5 hospital claims expense, 7,9 and improve quality of life 2,10 for people with chronic disease. There is also evidence of improved disease self-management, 11 a positive return on investment, 12 and cost-effectiveness 12,13 for people with cardiac failure and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that DM programs reduce hospital admissions, 3,[5][6][7][8] length of stay, [5][6][7] emergency room visits, 5 hospital claims expense, 7,9 and improve quality of life 2,10 for people with chronic disease. There is also evidence of improved disease self-management, 11 a positive return on investment, 12 and cost-effectiveness 12,13 for people with cardiac failure and diabetes.…”
Section: Introductionmentioning
confidence: 99%